THE FACTORS THAT AFFECTING THE SATISFACTION OF LIFE OF AGING IN THE VILLAGE JAMBAKAN BAYAT SUB DISTRICT KLATEN REGENCY - Tyas Wulandari; Yeni Rusyani; Ida Untari (STIKES DUTAGAMA KLATEN, 2015)
Background : Aging is said to be success in its life if it reached life satisfaction of life. The satisfaction of life are not only someone’s ability in enjoying their experiences but also person’s the level of excitement that arise frome needing everyday and the expectations to enjoy something. Objectives : The objectives of this researcd is to know the factors that affecting of the satisfaction of life of aging in the vilage Jambakan Bayat Klaten. Research Methodology : The method of this research is the Quantitative Descriptive, The researcd is held on November 2012 until Augustus 2013, the population of this researcd are all of aging between 45-59 years old the totally 450 persons, the sample that use 82 respondents, sample was take by purposive sampling. The instruments are used Check list and Kuesioner, the analize of data are used analize univariate with Mean and Modus. Results : The incoming factor that dominates the respondents 67 respondents (81.7%), the healting that dominates the respondents, the respondents that unill for 3 month as 70 respondents (85.4%), the social factors that dominates respondents are well as 60 respondents (73.2%). Conclusions : The incoming factor, health factors, social factors are affection the life satisfation of life.